Economic implications of biological therapy for Crohn’s disease - Petryszyn, Paweł W.; Paradowski, Leszek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
In the early 90s American authors estimated that if a theoretical new drug was introduced that was capable of changing the natural course of the disease and reducing direct non-drug medical costs (including hospitalisation and surgery) by 20%, despite doubling the overall drugs bill, there would still be a reduction in total direct medical costs of Crohn’s disease by 13%. Infliximab proved to be efficacious in reducing and maintaining remission in moderate to severe active Crohn’s disease and/or fistulising Crohn’s disease. A higher acquisition cost still remains its major limitation. Currently only the use of infliximab in case of treatment for flares seems to be cost-effective. However, this statement may be modified in the near future.